Studying Protein-DNA Interactions by Hydrogen/Deuterium Exchange Mass Spectrometry - Filandrova, Ruzena; Kavan, Daniel; Kadek, Alan; Novak, Petr; Man, Petr (Methods in molecular biology (Clifton, N.J.), 2021)
Protein hydrogen/deuterium exchange (HDX) coupled to mass spectrometry (MS) can be used to study interactions of proteins with various ligands, to describe the effects of mutations, or to reveal structural responses of proteins to different experimental conditions. It is often described as a method with virtually no limitations in terms of protein size or sample composition. While this is generally true, there are, however, ligands or buffer components that can significantly complicate the analysis. One such compound, that can make HDX-MS troublesome, is DNA. In this chapter, we will focus on the analysis of protein-DNA interactions, describe the detailed protocol, and point out ways to overcome the complications arising from the presence of DNA.
Keywords: vodík/deuteriová výměna a hmotnostní spektrometrie; Hydrogen Deuterium Exchange-Mass Spectrometry; Protein Binding; Transcription Factors; chromatografie kapalinová; Humans; transkripční faktory; zvířata; analýza dat; Chromatography, Liquid; Binding Sites; vazebná místa; Transcription factor; DNA-Binding Proteins; Data Analysis; Protein–DNA binding; Structural mass spectrometry; DNA vazebné proteiny; vazba proteinů; Protein Interaction Domains and Motifs; DNA; interakční proteinové domény a motivy; Animals; lidé; Hydrogen/deuterium exchange